Stability and stress analyses of headrace tunnel, Upper Seti Storage Hydroelectric Project, Western Nepal - Regmi, Niraj Kumar; Adhikary, Prakash Chandra; Tamrakar, Jayandra Man; Dhakal, Rabindra Prasad (Bulletin of the Department of Geology, 2008)
The Upper Seti (Damauli) Storage Hydroelectric Project has a capacity of 128 MW, the storage type scheme, and includes 1000 m long horse shoe headrace tunnel, 140 m high concrete gravity dam, two diversion tunnels of lengths 712 m and 881 m and an underground powerhouse. The study was carried out to identify stability and stress conditions for the headrace tunnel to suggest the required tunnel support. The project area extensively covers dolomite and minorly covers slate. The rock mass classification showed fair to good quality of dolomite and poor to fair quality of slate. The surface wedges would form in intake portal and powerhouse site. In the headrace tunnel, structural wedges would be formed due to underground excavation and would be stabilized with the help of shotcrete and rock bolting.   doi: 10.3126/bdg.v10i0.1419 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 45-54